Management of primary immune thrombocytopenia. A comparison between two historical cohorts - Sandra Fernández-Plaza; Jesús González de Pablo; Eva Gálvez; Josune Zubicaray; Julián Sevilla; Elena Sebastián (Elsevier, 2021)
Introduction: In recent years, there have been changes in the management of patients with primary immune thrombocytopenia. In this study, a review is presented of the characteristics and outcomes of children with primary immune thrombocytopenia in a children's hospital (Hospital Infantil Niño Jesús). Moreover, an analysis is made of the changes in the care of these patients diagnosed before and after 2011, when new guidelines were published by the Spanish Society of Paediatric Haematology Oncology (SEHOP). Material and methods: Data from a cohort of primary immune thrombocytopenia patients followed up in this hospital have been retrospectively reviewed. The statistical package used for the analysis was SPSS Statistics 22.0 (IBM Corp., Chicago, IL, USA). Results: A review is presented on the clinical data from 235 paediatric patients diagnosed with primary immune thrombocytopenia. It was observed that some features at diagnosis, such as age younger than five years and a previous history of infection, influenced the probability of cure. Regarding the changes in the management of patients since 2011, the steroid doses received during the first month and the first year, and the number of days corresponding to the patient's first admission have both significantly decreased. Splenectomies were also significantly reduced. Conclusions: Since 2011, there have been changes in the medical care of our primary immune thrombocytopenia patients: they receive lower doses of steroids, they stay fewer days in the hospital, and the number of splenectomies has decreased without increasing bleeding or worsening the clinical evolution. Furthermore, it was observed that age younger than 5 years and a history of infection prior to diagnosis were related to higher chances of recovery. Resumen: Introducción: En los últimos años se han experimentado cambios en el manejo de los pacientes con trombocitopenia inmune primaria. En este estudio se revisan las características de los pacientes con trombocitopenia inmune primaria del Hospital Infantil Universitario Niño Jesús y su evolución. Además, analizamos los cambios en el abordaje de los pacientes diagnosticados antes y después del 2011, año en el que se publicó la guía de la Sociedad Española de Pediatría. Material y métodos: Se han revisado retrospectivamente los datos de pacientes con trombocitopenia inmune primaria en seguimiento en nuestro hospital desde el año 2000. El paquete estadístico utilizado para el análisis fue SPSS Statistics 22.0 (IBM Corp, Chicago, IL, EE.UU.). Resultados: Se han revisado 235 pacientes pediátricos con trombocitopenia inmune primaria observando que algunas características al diagnóstico, como la edad menor de 5 años y los antecedentes previos de infección, pueden influir en la probabilidad de recuperación. Con respecto al cambio de manejo de los pacientes, a partir de 2011 las dosis de esteroides recibidas durante el primer mes y el primer año se han reducido de forma significativa, así como el número de días del primer ingreso pasando de 5 a 3 días. Las esplenectomías también se han reducido significativamente. Conclusiones: Desde el año 2011 se han producido cambios en el abordaje de nuestros pacientes: reciben una menor dosis de esteroides, permanecen menos días ingresados y se ha reducido el número de esplenectomías sin aumentar los sangrados y sin disminuir la tasa de respuestas. Además, observamos que la edad menor de 5 años y el antecedente de infección previa al diagnóstico están relacionados con una mayor tasa de recuperación.